Experimental investigation and mathematical modeling of oil/water emulsion separation effectiveness containing alkali-surfactant-polymer - Aleem, W. (Bellwether Publishing, Ltd., 2021)
Alkalis, surfactants and/or polymers are usually injected in the injector wells so that the injection fluids can sweep through the reservoir and mobilize/recover more oil. However, the formation of stable emulsion due to the residual chemicals in the recovered crude oil poses problems in the primary separation process. This study focuses on the effect of Alkali-Surfactant-Polymer injection on creaming and coalescence of crude oil and water emulsion produced in the primary gravity separator. In addition, a model is developed in this work to predict the separation effectiveness of oil and water emulsion containing ASP. In this work, the effect of ASP on the stability and the separation of crude oil water emulsion is investigated using the Turbiscan light transmission and back scattering device. The range of concentration of ASP used in this work is same as that found in the primary gravity separator. The investigation revealed that ASP plays an important role in the stability of the emulsion. A new model based on Stokes law and incorporating coalescence phenomena for the prediction of separation profile of oil and water in terms of separated layer profile is developed. The model is validated with experimental data obtained from the Turbiscan light transmission and backscattering device. The model is able to predict the separation profile of an oil-water emulsion containing ASP with excellent agreement. Â© 2020 Taylor & Francis Group, LLC.